Sociodemographic determinants and risk factors of sudden cardiovascular death - Rafael E. Araujo González; Luis Alberto Ochoa Montes; Rubén Herrera Masó (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Cardiovascular diseases represent the leading cause of death in the world; specifically, sudden cardiovascular death causes 50% of all deaths from this cause. Objective: to describe the correlation between sociodemographic variables and risk factors in sudden cardiovascular death. Methods: a descriptive, correlational and cross-sectional study was carried out in the Havana municipality of Arroyo Naranjo, between 2007 and 2014. All cases of sudden cardiovascular death were included, treated at the Julio Trigo López Teaching Clinical-Surgical Hospital (N =605). Sociodemographic variables and risk factors were analyzed. The Chi-square statistical test and the Haberman Corrected Waste model were used. Results: in men, especially in black and mestizo skin, the most frequent risk factors were smoking, alcohol consumption and high blood pressure. Women were characterized by more physical inactivity, and were more affected by diabetes, dyslipidemias and elevated hematocrit values. Most of the deceased did not exceed secondary education, technical level or skilled worker. Conclusion: Sudden cardiovascular death, in the municipality of Arroyo Naranjo, Havana, essentially affects people over 50, a period of life in which risk factors such as hypertension, smoking and physical inactivity impact greater on mortality.